AGRIVIGIL: ENHANCED THEFT DETERRENCE FOR IRRIGATION MACHINERY - Prof. Shaikh A. H. A.R.; Mr. Harsh Gajul; Mr. Avinash Inde; Miss. Nida Dharwadkar; Mr. Omdeep Pujari (International Journal of Innovations in Engineering Research and Technology, 2024)
The rampant theft of water pumps in rural India poses a severe challenge to farmers, significantly undermining their irrigation capabilities and, by extension, crop health and productivity—particularly in regions susceptible to unpredictable rainfall and drought. This theft not only inflicts immediate equipment loss but also propels farmers, who typically operate within narrow financial margins, into further economic hardship due to the inability to afford replacements. The consequent delays in planting and irrigation lead to reduced crop yields and heightened financial strain. The vulnerability of these essential tools is amplified by the remote locations of farms and a pronounced lack of security measures, rendering water pumps an easy target for thieves. This dire situation underscores the urgent need for a comprehensive water pump theft deterrence system, which is essential not only for protecting valuable agricultural equipment but also for safeguarding the livelihoods of farmers. By leveraging advanced technology to provide real-time alerts and deter potential thefts, such a system can serve as a critical defence mechanism, enabling farmers to concentrate on their vital work without the looming threat of loss. The implementation of effective theft deterrence measures, supported by community, law enforcement, and policy maker collaboration, is crucial in ensuring the economic well-being and sustainability of rural Indian agriculture.